Teaching Young Learners’ Listening Skills with Advantageous Activities (Zien Journal of Social Sciences and Humanities, 2022)
This research deals with advantageous activities for teaching listening skill of young learners. “Young learners” includes ages from 7 to 12 years old and if they are under 7 years old are named “Very young learners”. So this article surely helps teachers who are teaching ages from 5 to 12 years old. The article provides variety of practical advises and activities based on listening skill of children for teaching young learners.